FROM ONBOARDING TO OFFBOARDING: CREATING A COHESIVE EMPLOYEE LIFECYCLE JOURNEY - Wiranto Timotius Situmorang; Sri Langgeng Ratnasari; Firdaus Hamta (RADJA PUBLIKA, 2026)
In today’s competitive and dynamic business environment, organizations are increasingly recognizing the importance of delivering a cohesive employee experience across the entire lifecycle. This study examines how human resource management practices can be integrated from onboarding to offboarding to create a seamless and consistent employee journey. Drawing on a conceptual and qualitative review of academic literature, HR reports, and case studies, the paper identifies key practices that enhance lifecycle integration, including structured onboarding, continuous development, performance management, and effective offboarding strategies. The findings highlight that fragmented HR processes can undermine employee engagement, while a holistic lifecycle approach fosters consistency, alignment, and long-term commitment. The study also emphasizes the role of leadership, organizational culture, and technology in enabling integration and continuity. By adopting a lifecycle perspective, organizations can improve employee satisfaction, retention, and overall performance. A conceptual framework is proposed to illustrate how integrated HR practices contribute to enhanced employee experience and organizational outcomes. The study contributes to the HRM and employee experience literature by offering a comprehensive view of lifecycle management. It concludes that organizations must move toward integrated, employee-centered strategies to remain competitive and sustainable.